Rozwijanie refleksyjności nauczycieli języków obcych na przykładzie techniki analizy zdarzeń krytycznych. Studium przypadku - Kiliańska-Przybyło, Grażyna (Neofilolog, 2019)
The article aims at presenting the technique of critical incidents analysis as a tool to promote reflectivity among inexperienced foreign language teachers. Critical incidents, often used in social and educational studies, are defined as meaningful and important situations (both positive and negative) that trigger individual’s reflection and help him/her realize his/her beliefs and practices. The article provides characteristics of the technique of critical incidents analysis. Data gathered from inexperienced student teachers (n= 30) indicate strong emotional involvement of the subjects in the study . Their descriptions of critical incidents concentrated mostly on negative situations resulting from their lack of experience with classroom routines, low self-confidence and feelings of inadequacy. „Nauczanie to uczestniczenie w powodzi zdarzeń” (Tripp 1993; Kwiatkowska 2008: 173)